2010
DOI: 10.1073/pnas.0912955107
|View full text |Cite
|
Sign up to set email alerts
|

“Control” laboratory rodents are metabolically morbid: Why it matters

Abstract: Failure to recognize that many standard control rats and mice used in biomedical research are sedentary, obese, glucose intolerant, and on a trajectory to premature death may confound data interpretation and outcomes of human studies. Fundamental aspects of cellular physiology, vulnerability to oxidative stress, inflammation, and associated diseases are among the many biological processes affected by dietary energy intake and exercise. Although overfed sedentary rodents may be reasonable models for the study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
231
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(247 citation statements)
references
References 104 publications
6
231
1
1
Order By: Relevance
“…In rodents, daily food intake reduction of 20-40 % significantly reduces WAT (Blüher et al 2003), the risk to develop CVD, or other age-associated diseases (Martin et al 2010) and extends life span by up to 40 % (Barzilai et al 1998). Equivalent findings were observed in humans considering that 1 year of low-energy diet reduces markedly atherosclerosis risk factors such as high body mass index, blood pressure, blood levels of glucose, insulin, CRP, TG, and LDL-c, and increases the levels of HDL-c (Fontana et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, daily food intake reduction of 20-40 % significantly reduces WAT (Blüher et al 2003), the risk to develop CVD, or other age-associated diseases (Martin et al 2010) and extends life span by up to 40 % (Barzilai et al 1998). Equivalent findings were observed in humans considering that 1 year of low-energy diet reduces markedly atherosclerosis risk factors such as high body mass index, blood pressure, blood levels of glucose, insulin, CRP, TG, and LDL-c, and increases the levels of HDL-c (Fontana et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the association between increased risk of developing AD and excess body weight reflects the potential effect of a diet high in simple sugars and fats to the development of AD. A recent study showed reducing caloric intake increases healthspan, reduces damage in the brain due to aging, and provides greater maintenance of various brain functions (Martin et al, 2008; Martin, Golden, Egan, Mattson, & Maudsley, 2007; Martin, Ji, Maudsley, & Mattson, 2010; Martin, Mattson, & Maudsley, 2006). …”
Section: Lifestyle Associations and Interventions For Aging And Admentioning
confidence: 99%
“…However, Martin et al [20] have voiced strong concerns that 'control' mice are in fact 'sedentary, obese and glucose intolerant' and cautioned that this has great potential to 'confound data interpretation on outcomes of human studies.' The authors note that lack of exercise and unlimited access to food are major culprits.…”
Section: Glossarymentioning
confidence: 99%